STRATEGIES TO IMPROVE EMPLOYEE PERFORMANCE DURING THE COVID-19 PANDEMIC THROUGH MOTIVATION AND LEADERSHIP STYLE MEDIATED BY JOB SATISFACTION - Atikah, Selvi; Esti Riwayati, Hedwigis (Dinasti International Journal of Management Science, 2021)
This study aims to analyze strategies to improve employee performance during the pandemic through motivation and leadership style mediated by job satisfaction of PT Hanwa Indonesia employees during the Covid 19 pandemic. The data used is primary data obtained by distributing questionnaires. The population uses 160 employees of PT Hanwa Indonesia. The sample is 114 employees. Data processing using the PLS-SEM model. The results showed that work motivation and leadership style had a significant positive effect on job satisfaction. Work motivation and leadership style have no effect on employee performance. Job satisfaction has a significant positive effect on employee performance. Job satisfaction is not able to mediate the influence of motivation and leadership style on the performance of PT Hanwa Indonesia employees during the Covid 19 pandemic.